The Role of the Beta-Amyloid Precursor Protein in the Diagnosis of Diffuse Axonal Injury - Davcheva, N; Dimitrova, M; Kadiysky, D; Grozeva, M; Basheska, N (Bulgarian Academy of Sciences, Prof. Marin Drinov Publishing House, 2015)
Diffuse axonal injury (DAI) is a distinct clinical-pathological entity in the closed head injuries, where very often, the macroscopic lesion of the brain tissue cannot be found. Hence, in those cases the microscopic examination is of a huge importance. Using the conventional staining techniques the axonal injuries can be perceived only if there has been a survival of up to 24 hours (hematoxylin and eosin staining), or 12 to 18 hours (silver impregnation methods). With the introduction of immunohistochemistry using antibodies against β-Amyloid Precursor Protein (β-APP), this period has been shortened to 3 hours, even less. In the present paper, a review on the role of β-APP immunohistochemistry in the diagnosis of DAI is presented. This review shows that β-APP immunohistochemistry can be a very powerful tool in diagnosing the axonal injuries, what is of a special significance for the forensic medicine practice.
Keywords: diffuse axonal injury; β-amyloid precursor protein; immunohistochemistry; forensic medicine.